2005
DOI: 10.1111/j.1469-7580.2005.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Deer antlers: a zoological curiosity or the key to understanding organ regeneration in mammals?

Abstract: Many organisms are able to regenerate lost or damaged body parts that are structural and functional replicates of the original. Eventually these become fully integrated into pre-existing tissues. However, with the exception of deer, mammals have lost this ability. Each spring deer shed antlers that were used for fighting and display during the previous mating season. Their loss is triggered by a fall in circulating testosterone levels, a hormonal change that is linked to an increase in day length. A complex 'b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
166
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(173 citation statements)
references
References 90 publications
2
166
1
4
Order By: Relevance
“…Among ruminant headgear, the antler has prompted the most study in part because it is capable of periodically regenerating after complete abscission. The antler is a bony outgrowth from the lateral crest of the frontal bone [20,62]. During growth, the integument and underlying subcutaneous loose connective tissue (SLCT) externally cover the antler [20,41]; interactions between the external and internal tissues are vital to the initiation and modulation of longitudinal growth [63].…”
Section: Histogenesis Of Ruminant Headgearmentioning
confidence: 99%
See 1 more Smart Citation
“…Among ruminant headgear, the antler has prompted the most study in part because it is capable of periodically regenerating after complete abscission. The antler is a bony outgrowth from the lateral crest of the frontal bone [20,62]. During growth, the integument and underlying subcutaneous loose connective tissue (SLCT) externally cover the antler [20,41]; interactions between the external and internal tissues are vital to the initiation and modulation of longitudinal growth [63].…”
Section: Histogenesis Of Ruminant Headgearmentioning
confidence: 99%
“…By contrast, sharp differences in their development and physiology have led to hypotheses of multiple origins (table 1). Antlers (figure 2a), found only in cervids, are composed of exposed, living bone when mature [16] and are unique among mammalian appendages in their ability to completely and periodically regenerate in adults [17][18][19][20]. Horns (figure 2b), found only in bovids, are composed of a scabbard-like keratinous sheath covering a bony horncore, neither of which is ever shed [14,21].…”
Section: Introductionmentioning
confidence: 99%
“…As the days shorten in late summer, plasma testosterone levels rise, the velvet is shed and antlers become heavily mineralized for the autumn mating season (Price et al, 2005a). However, several reports have indicated that estrogen is actually synthesized by antler tissues in deer stags (Barrell et al, 1999;Bubenik et al, 2005) and that testosterone might have an indirect role on antler cells in vivo, via its conversion to estrogen by aromatase (Price et al, 2005b). Interestingly, it has been demonstrated that estrogen induces the expression of BDNF and its receptors in the brain (Numakawa et al, 2010) and also in the uterus (Wessels, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Antlers are indeed astonishing structures, renewed annually over a relatively short period, with their growth making huge demands on the buck's physiology, in preparation for the autumn rut, when males use their antlers for display and in combat for the right to mate with a group of females. They represent one of the fastest-growing mammalian tissues, developing as much as 14 kg in a 6 month period, with a peak growth rate of 2-4 cm per day (Chen, Stokes and McKittrick 2009), although one estimate states that the antlers of a 200 kg red deer (Cervus elaphus) stag can reach a weight of 30 kg and grow in only three months (Price et al 2005). Unlike horn, which consists of keratinized tissue over a bony core, antlers comprise skin, nerves, blood vessels, fibrous tissue, cartilage and bone (Price et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…They represent one of the fastest-growing mammalian tissues, developing as much as 14 kg in a 6 month period, with a peak growth rate of 2-4 cm per day (Chen, Stokes and McKittrick 2009), although one estimate states that the antlers of a 200 kg red deer (Cervus elaphus) stag can reach a weight of 30 kg and grow in only three months (Price et al 2005). Unlike horn, which consists of keratinized tissue over a bony core, antlers comprise skin, nerves, blood vessels, fibrous tissue, cartilage and bone (Price et al 2005). They are remarkable in many respects: in their rate of growth, in their ability to regenerate, and for their role in the social life of deer.…”
Section: Methodsmentioning
confidence: 99%